DETERMINANTS OF LEVEL OF ECONOMIC EFFICIENCY OF RICE PRODUCERS IN ANAMBRA STATE, NIGERIA - N. R , CHIEKEZIE,; N. J , Obiekwe,; C.O.A , Ugwumba,; M. U , Ozor, (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
This study examined determinants and level of economic efficiency of rice production in Anambra State, Nigeria. The specific objectives were to: estimate the level of economic efficiency attained by rice farmers in the area; ascertain the determinants of level of economic efficiency attained by the farmers and assess the nature of returns to scale of rice production in the study area. Two hypotheses tested were: there is no significant difference between the levels of economic efficiency attained by farmers in the selected agricultural zones and socio-economic characteristics of the rice farmers do not significantly influence their economic efficiency level. Primary data were used for the study and Multistage, purposive and random sampling methods were used select 378 respondents. The collated data were analyzed by means of descriptive and inferential statistical tools such as Ordinary Least Squares (OLS) regression, Cobb Douglas Stochastic Frontier Production function and Scheffe’s Multiple Comparison test. Findings indicated a minimum economic efficiency score of 0.86, maximum of 0.99 and mean of 0.95 for rice farmers in the study area. Scheffe’s Multiple Comparison test indicated significant difference between means of economic efficiency scores and per hectare profits of farmers from paired agricultural zones. Maximun Likelihood Estimation of the Cobb Douglas stochastic frontier production regression showed that the production factors of land, labour and other inputs significantly and positively influenced economic efficiency level of the farmers. Inefficiency effect was significantly and negatively affected by educational level and amount of credit obtained; significantly and positively affected by farming experience while extension visit and farm size were not significant. Returns to scale figures were 1.32, 1.25, 1.15 and 1.12 for Anambra, Aguata and Awka Agricultural zones, and the State (pooled data) respectively. This implies increasing returns to scale across the Agricultural zones and the study area. It is recommended that Government should ensure adequate budgetary allocations to the institutions responsible for making cheap loans available to farmers while the institutions should maintain timely disbursement of the funds.